How Bi‐Modal Are Jupiter's Main Aurora Zones?. Issue 4 (26th April 2023) - Mauk, B. H.; Szalay, J. R.; Allegrini, F.; Bagenal, F.; Bolton, S. J.; Clark, G.; Connerney, J. E. P.; Gladstone, G. R.; Haggerty, D. K.; Kollmann, P.; Kurth, W. S.; Paranicas, C. P.; et al.
Abstract: Using Juno‐measured >30 keV electrons, three regions with substantial ultraviolet emissions were identified previously for Jupiter's main aurora (excluding the polar cap): low‐latitude diffuse aurora, mid‐latitude Zone I of downward acceleration, and higher latitude Zone II of bi‐directional acceleration. Zone I, associated with upward magnetic field‐aligned currents, was represented as bimodal: sometimes supporting coherent downward electron electrostatic acceleration and sometimes downward electron broadband acceleration, with broadband acceleration usually delivering the most intense electron energy flux at Juno. Recent observations of up‐going ion beams within Zone I represent a challenge as to whether coherent electrostatic acceleration invariably accompanies broadband acceleration. Is this region strictly bi‐modal, or is there a continuum between these two modes? We address these questions by combining multiple ion and electron data sources to diagnose electrostatic potentials both above and below the spacecraft. We find: (a) During Zone I downward electron broadband events, there are examples where evidence of downward electron electrostatic acceleration completely disappears and examples where it endures at some level. (b) Most often, evidence of downward electron electrostatic acceleration is strongly suppressed with strong downward electron broadband acceleration. Residual potentials most often (not always) have values small (<10 kV) compared to the electron characteristic energies of 100–400 keV. (c) Care must be exercised in these studies because plasmasheet electron precipitation spectra can mimic broadband acceleration spectra. At least for weaker auroral broadband accelerations, there is likely to be a continuum of electrostatic and broadband participation. Why either process is favored at any one time is unknown. Key Points: Zone I downward electron broadband acceleration sometimes has upward electrostatic potentials fully disappearing and other times enduring Zone I potentials of 30–360 kV often disappear to <10 kV with strong broadband electrons having characteristic energies of 100–400 keV Why one process (electrostatic or broadband) is favored over the other at any one time remains unknown